Corporate Environmental Performance and Competitiveness A Critical Review and an Empirical Study - Salem, Milad Abdelnabi; Hasnan, Norlena; Osman, Nor Hasni; Shamsudin, Mohd Farid; Shawtari, Fekri; Hussain, Hafezali Iqbal (India Publications, 2015)
There is an ongoing debate among environmental studies about whether being green affects corporate performance. The paper argues that the main reason for inconsistency in earlier results on this topic is the isolated use among previous studies of different types of environmental indicators, which made it difficult to identify general relationships between green indicators and business performance. Accordingly, we distributed questionnaires covering numerous items related to corporate environmental performance to determine the harmful environmental effects caused by corporate activities, and to ascertain areas of competitiveness strongly influenced by environmental issues. Following this, we empirically test the relationship between environmental performance and environmental competitiveness within 160 industrial organisations. The results indicated that environmental competitiveness could be explained by environmental performance. Several recommendations are addressed to be studied by future studies